Risk of Dementia or Cognitive Impairment in Sepsis Survivals: A Systematic Review and Meta-Analysis - Lei, Siyuan; Li, Xuanlin; Zhao, Hulei; Feng, Zhenzhen; Chun, Liu; Xie, Yang; Li, Jiansheng (Frontiers in Aging Neuroscience, 2022)
Background: There is growing evidence that sepsis survivals are at increased risk of developing new-onset atrial fibrillation, acute kidney injury, and neurological diseases. However, whether sepsis survivals increases the risk of dementia or cognitive impairment remains to be further explored. Objective: To determine whether sepsis survivals increase the risk of dementia or cognitive impairment. Methods: We searched PubMed, Cochrane Library, Web of Science and EMBASE databases for cohort studies or case-control studies from their inception to November 5, 2021. The quality of the study was assessed using the Newcastle-Ottawa Quality Assessment Scale (NOS). Stata software (version 15.1) was used to calculate the odds ratio (OR) of dementia or cognitive impairment in sepsis survivals. Subgroup and sensitivity analyses were performed to assess the source of heterogeneity. Funnel plots and Egger's test were used to detect the publication bias. Results: Eight studies (seven cohort studies and one case-control study) involving 891,562 individuals were included. The quality assessment results showed that the average score of NOS was over 7, and the overall quality of the included studies was high. Pooled analyses indicated that sepsis survivals were associated with an increased risk of all-cause dementia (OR=1.62, 95% confidence interval [CI]=1.23–2.15, I2=96.4%, P=0.001). However, there was no obvious association between sepsis survivals and the risk of cognitive impairment (OR=1.77, 95% CI=0.59–5.32, I2=87.4%, P=0.306). Subgroup analyses showed that severe sepsis was associated with an increased risk of dementia or cognitive impairment (OR=1.99, 95% CI=1.19–3.31, I2=75.3%, P=0.008); such risk was higher than that of other unspecified types of sepsis (OR=1.47, 95% CI=1.04-2.09, I2=97.6%, P=0.029). Conclusions: Sepsis survivals are associated with an increased risk of all-cause dementia, but not with that of cognitive impairment. Appropriate management and prevention are essential to preserve the cognitive function of sepsis survivors and reduce the risk of dementia